Emergency department asthma diagnosis risk associated with the 2012 heat wave and drought in Douglas County NE, USA - Figgs, Larry W. (Heart & lung, 2019)
Global climate change concerns are forcing local public health agencies to assess potential disease risk. Determine if risk of an emergency department asthma diagnosis in Douglas County, NE, was higher during the 2012 heatwave compared to 2011. Retrospective, observational, case-control design selecting subjects from 2011 and 2012 emergency department (ED) admissions. Risk was estimated by conditional logistic regression. The asthma ED risk estimate was 1.23 (95%CI = 0.96–1.57) times higher in 2012 than 2011, for the same calendar period. Asthma ED diagnosis risk was 3.37 (95%CI = 2.27–4.17) times higher among subjects <19years old compared to older subjects, and 3.25 (95%CI = 2.63–4.02) times higher among African-Americans than non-African–Americans, adjusted for heatwave exposure. Absolute humidity appears inversely related to asthma diagnosis risk ( χ2 = 16.6; p < 0.001). Asthma ED diagnosis risk was not significantly higher in 2012 compared to 2011. Risk was elevated among subjects less than 19years old, and among African Americans; adjusted for heatwave exposure.